The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1063/5.0048210
|View full text |Cite
|
Sign up to set email alerts
|

Reaction zone structure and detonation parameters of nitromethane/polymethylmethacrylate and its mixture with microballoons

Abstract: In the present work, the detonation wave structure and detonation parameters for nitromethane (NM) and its mixtures with polymethylmethacrylate (PMMA) and glass microballoons (GMB) were studied by a velocity interferometer system for any reflector laser interferometer. The PMMA concentration varied from 2% to 4%. It is shown that PMMA additives lead to a change in the reaction zone structure, which can be observed as an appearance of a cellular instability of the detonation front. The detonation parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The experimental studies of steady-state detonation waves in CL-20 show that the structure of the chemical reaction zone corresponds to the Zeldovich-von Neumann-Döring theory [38][39][40], assuming the existence of the von Neumann spike. The determination of the characteristic reaction time was not carried out in this work, since in order to accurately find this value, a special series of experiments are required to be conducted, e. g. [41]. Nevertheless, based on the obtained particle velocity profiles, it is concluded that this time is about 50 ns at the CL-20 initial density of 1.98 g/cm 3 .…”
Section: Steady-state Detonation Of Cl-20mentioning
confidence: 99%
“…The experimental studies of steady-state detonation waves in CL-20 show that the structure of the chemical reaction zone corresponds to the Zeldovich-von Neumann-Döring theory [38][39][40], assuming the existence of the von Neumann spike. The determination of the characteristic reaction time was not carried out in this work, since in order to accurately find this value, a special series of experiments are required to be conducted, e. g. [41]. Nevertheless, based on the obtained particle velocity profiles, it is concluded that this time is about 50 ns at the CL-20 initial density of 1.98 g/cm 3 .…”
Section: Steady-state Detonation Of Cl-20mentioning
confidence: 99%
“…To evaluate the contribution of microencapsulated explosives to an energetic formulation, detonation studies were performed; and results were compared to similar tests using a variety of inert additives. Hard, high-melting additives, such as glass microspheres or balloons, may aid the initiation of explosive formulations by acting as hot spot nucleation points for the growth and propagation of detonation, but they also sensitize the formulation to impact and friction [13,14]. Chemically inert, glass microballoons have been reported to increase the detonation velocity in an ammonium nitrate emulsion explosive [15].…”
Section: Introductionmentioning
confidence: 99%